PERSEPSI KOMUNITAS “ARSENAL” BANDUNG TERHADAP PESAN PERINGATAN PADA BUNGKUS ROKOK - Muhammad Hanif Ahda (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2019)
Cigarettes are the product that leads to the pros and cons the people of Indonesia. Negative effects due to smoking no doubt, substances in cigarettes to be an indicator of various diseases of cigarettes to consumers. The government has issued a rule requiring cigarette manufacturers to the dangers of smoking message by including images warning of the dangers of smoking. This study aims to determine the perceptions of community members regarding visual warning label smoked edition of "lungs damaged". Data collection techniques used in this research through interviews, observation, documentation. This study refers to the theories of perception ecology, how the stages of processing human perception occurs, that man's way of responding to a stimulus environmental, cultural backgrounds and communities, through the method of the message fear appeals, on delivery through media spooky image on cigarette packs. Results of research conducted by researchers at the community Arsenal Indonesian Supporter is a positive perception of the members of that community, and the message delivered by the government through the media picture warnings to be put on artificial cigarette packs in particular edition of "lungs damaged" conveyed properly, it is evident by reduced consumption rate of smokers in the community. Thus, it can be concluded that government regulation regarding the rules for the inclusion of the dangers of smoking images on cigarette packs is a good effort although still not very effective but enough make community members AIS Bandung smokers reduce smoking intensity and some have quit smoking.